2020
DOI: 10.1136/lupus-2020-000399
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and neutropaenia: a hallmark of haematological manifestations

Abstract: ObjectiveSystemic lupus is a chronic autoimmune disease characterised by its phenotypic heterogeneity. Neutropaenia is a frequent event in SLE occurring in 20%–40% of patients depending on the threshold value of neutrophil count. On a daily basis, the management of neutropaenia in SLE is difficult with several possible causes. Moreover, the infectious consequences of neutropaenia in SLE remain not well defined.Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
2
6
1
2
Order By: Relevance
“…There was also no significant association between any autoantibody against nuclear antigens and neutropenia in a study including 82 lupus erythematosus patients [ 18 ]. A study including 208 SLE patients with neutropenia and 779 SLE patients without neutropenia showed that neutropenia was significantly associated with thrombocytopenia, lymphopenia, and low levels of complement C3 as determined in a multivariate analysis, which was similar to our results [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…There was also no significant association between any autoantibody against nuclear antigens and neutropenia in a study including 82 lupus erythematosus patients [ 18 ]. A study including 208 SLE patients with neutropenia and 779 SLE patients without neutropenia showed that neutropenia was significantly associated with thrombocytopenia, lymphopenia, and low levels of complement C3 as determined in a multivariate analysis, which was similar to our results [ 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…Most leucopenia episodes were driven by lymphopenia, which is recognized as the most common white blood cell abnormality among lupus patients [ 1 ]. Neutropenia was observed at least once in 12.5% of patients, lower than a recently reported European cohort [ 15 ], and occurred in 3.4% of visits. Severe neutropenia was rare (0.95%).…”
Section: Discussioncontrasting
confidence: 63%
“…The study was done across multiple Asia Pacific lupus centres and is therefore a predominantly Asian cohort (89%). Genetic factors relating to ethnicity can certainly influence the severity and frequency of leucopenia; for example, we have already seen that our cohort had a lower frequency of neutropenia compared with another recent report of lupus patients in Europe [ 15 ]. Our findings, however, are still largely generalizable, as the overall prevalence of lymphopenia (which made up the majority of leucopenia), the patterns of disease activity and medication use were all similar to other cohorts.…”
Section: Discussionmentioning
confidence: 69%
“…Neutropenia was reported to occur in 20-47% of the patients with SLE [2,6,11,12]. A recent large multicentric registry (Lupus BioBank of the upper Rhein) found a prevalence of 21% of neutropenia in Caucasian SLE that was significantly associated with thrombocytopenia (OR 3.68 [2.58-5.25 [1.96-4.32], p < 0.0001) [13]. Among other causes of neutropenia in SLE patients, benign ethnic (familial) neutropenia, which is one of the most common causes of chronic neutropenia seen in individuals of African, Middle Eastern, and west Indian descent [14], should be excluded before attributing lupus as the cause of neutropenia.…”
Section: Leukopenia In Systemic Lupus Erythematosusmentioning
confidence: 99%